2016
DOI: 10.1111/den.12597
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal endoscopic submucosal dissection: Systematic review of mid‐term clinical outcomes

Abstract: With a drive towards minimally invasive surgery, endoscopic submucosal dissection (ESD) is now gaining popularity. In a number of East Asian countries, ESD is now the treatment of choice for early non-metastatic gastric cancer, but the outcomes of ESD for colorectal lesions are unclear. The present review summarizes the mid-term outcomes of colorectal ESD including complication and recurrence rates. A systematic literature search was done in May 2014, identifying 20 publications reporting the outcomes of color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 47 publications
4
38
0
2
Order By: Relevance
“…Three recent studies on ESD for UC‐associated dysplasia have reported en bloc resection rates of 80–100% and R0 resection rates of 70–76% . These results are comparable with the outcomes summarized in the systematic reviews of ESD for almost exclusively sporadic CRN ( en bloc resection rates of 89–92% and R0 resection rates of 76–83%) . However, the R0 resection rate for ESD of UC‐associated dysplasia seems relatively lower than the pooled R0 resection rate of 85.6% reported previously in an Asian subgroup .…”
Section: Discussionsupporting
confidence: 71%
“…Three recent studies on ESD for UC‐associated dysplasia have reported en bloc resection rates of 80–100% and R0 resection rates of 70–76% . These results are comparable with the outcomes summarized in the systematic reviews of ESD for almost exclusively sporadic CRN ( en bloc resection rates of 89–92% and R0 resection rates of 76–83%) . However, the R0 resection rate for ESD of UC‐associated dysplasia seems relatively lower than the pooled R0 resection rate of 85.6% reported previously in an Asian subgroup .…”
Section: Discussionsupporting
confidence: 71%
“…The Japanese Colorectal ESD Standardization Implementation Working Group recommends the following indications for colorectal ESD: large lesions (> 20 mm) suspicious for high-grade intraepithelial neoplasia or early cancer, lesions that display fibrosis including sporadic adenomas in chronic inflammation or residual carcinoma after previous endoscopic therapy[12]. Patel et al[13] reviewed the outcomes of colorectal ESD and found that it results in en bloc resection, complete resection, and recurrence rates of 89%, 76%, and 1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) is an effective procedure for the treatment of large colorectal lesions, with excellent en‐bloc resection and local recurrence rates . In large and bulky lesions, however, retrieval of the specimen may be challenging.…”
Section: Brief Explanationmentioning
confidence: 99%
“…is an effective procedure for the treatment of large colorectal lesions, with excellent en-bloc resection and local recurrence rates. 1 In large and bulky lesions, however, retrieval of the specimen may be challenging. Various approaches have been advocated for this situation including use of a small grip-seal plastic bag, 2 or defecation by rectal enema.…”
mentioning
confidence: 99%